Achieving the composite endpoint of HbA1c, body weight, and systolic blood pressure reduction with canagliflozin in patients with type 2 diabetes. (1st February 2018) - Merton, Katherine; Davies, Michael J.; Vijapurkar, Ujjwala; Inman, Doreen; Meininger, Gary
Abstract: Objective: In addition to achieving glycemic control, weight loss and blood pressure (BP) reduction are important components of type 2 diabetes mellitus (T2DM) management, as many patients with T2DM are overweight/obese and/or have hypertension. Canagliflozin, an SGLT2 inhibitor, has demonstrated improvements in HbA1c, body weight (BW), and systolic BP across a broad range of patients with T2DM. This analysis evaluated achievement of composite endpoints of HbA1c, BW, and systolic BP targets with canagliflozin versus placebo. Methods: This post hoc analysis evaluated the proportion of T2DM patients achieving the composite endpoint of HbA1c reduction ≥0.5%, BW reduction ≥3%, and systolic BP reduction ≥4mmHg with canagliflozin 100 and 300mg compared with placebo using pooled data from four 26-week, phase 3 studies ( N  = 2313; NCT01081834, NCT01106677, NCT01106625, NCT01106690). The proportion of patients achieving the composite endpoint of HbA1c <7.0%, BW reduction ≥3%, and BP <130/80 mmHg was also evaluated. Results: At week 26, greater proportions of patients met individual HbA1c, BW, and systolic BP targets with canagliflozin versus placebo. A greater proportion of patients treated with canagliflozin 100 or 300 mg versus placebo also achieved the composite endpoint of HbA1c reduction ≥0.5%, BW reduction ≥3%, and systolic BP reduction ≥4 mmHg at week 26 (21.1%, 25.3%, and 5.7%, respectively; odds ratios [95% CI] of 4.5 [3.1, 6.5] and 5.6 [3.8, 8.2]). A greater proportion of patients also achieved the composite endpoint of HbA1c <7.0%, BW reduction ≥3%, and BP <130/80 mmHg with canagliflozin 100 and 300 mg versus placebo (14.7%, 20.9%, and 3.3%, respectively; odds ratios [95% CI] of 5.2 [3.2, 8.4] and 8.4 [5.2, 13.5]). Canagliflozin was generally well tolerated, with a safety profile similar to that seen in other phase 3 studies. Conclusions: Patients with T2DM were more likely to achieve clinically important reductions in HbA1c, BW, and systolic BP with canagliflozin versus placebo.